The counter administrative decision and its applications in the Board of Grievances in the Kingdom of Saudi Arabia - Al-Thaqafi, Abdul Majeed Abdullah Khalifa (Journal of Economic, Administrative and Legal Sciences, 2024)
This research aims to study the concept of the administrative appeal and its applications in the Grievance Board in the Kingdom of Saudi Arabia. The research includes several topics and demands that aim to study the administrative appeal and analyze the legal mechanisms followed in the administrative appeal procedures in Saudi Arabia. The research aims to understand the concept of the administrative appeal and distinguish it from other decisions, as well as to draw the opinions of jurists and judges on its characteristics. The research includes several sub-claims that address the legal foundations and characteristics of the administrative appeal decision, its issuing authority, and the legal mechanisms for appealing administrative appeal decisions in Saudi Arabia, as well as the role of the administrative judiciary in reviewing administrative appeal decisions. The research also discusses the impact of the administrative appeal decision on government entities and citizens in Saudi Arabia, analyzes the legal results and effects of court decisions regarding appeals against administrative appeal decisions in the Kingdom of Saudi Arabia. The research is characterized by its focus on monitoring legal developments related to the administrative appeal decision and its application in Saudi Arabia, and aims to enrich legal knowledge related to this important topic.